Seroconversion panels demonstrate anti-SARS-CoV-2 antibody development after administration of the mRNA-1273 vaccine. Issue 22 (11th May 2022) - Belda, Francisco; Mora, Oscar; Lopez Martinez, Monica; Torres, Nerea; Vivanco, Ana; Christie, Rebecca; Crowley, Michael
Highlights: Two seroconversion panels from samples before and after vaccination with mRNA-1273 vaccine. Subjects positive for IgG prior to vaccination had a higher response to the first vaccination. Responses to the first dose of vaccine were lower in naïve elderly subjects. All subjects had positive responses after the second vaccine dose. Seropositive or convalescent subjects may be sufficiently protected after one dose of vaccine. Abstract: Seroconversion panels are an important tool for investigating antibody responses in acute and chronic phases of disease and development of serological assays for viral diseases including COVID-19. Globally it is anticipated that vaccines against SARS-CoV-2 will facilitate control of the current pandemic. The two COVID-19 seroconversion panels analyzed in this study were obtained from healthcare workers with samples collected before vaccination with the mRNA-1273 vaccine (Moderna) and after the first and second doses of the vaccine. Panel samples were tested for antibodies to SARS-CoV-2 (IgG). Individual subjects with a positive response for anti-SARS-CoV2 IgG in their pre-vaccination samples showed a significantly enhanced response to the first vaccination. In older subjects, lower immunological responses to the first injection were observed, which were overcome by the second injection. All subjects in the study were positive for anti-SARS-CoV-2 IgG after the second dose of vaccine.